Reservoir characteristics and critical influencing factors on gas hydrate accumulations in the Shenhu area, South China Sea. (November 2021) - Wang, Dongdong; Ning, Fulong; Lu, Jingan; Lu, Hongfeng; Kang, Dongju; Xie, Yingfeng; Li, Jing; Sun, Jiaxin; Ou, Wenjia; Liu, Zhichao; Fang, Bin; Peng, Li; et al.
Abstract: The Shenhu area is the key target area for marine gas hydrate industrialization in China. Significant progress has been made with respect to gas hydrate exploration and production in this area in recent years. However, a comprehensive understanding of the reservoir characteristics and hydrate accumulation mechanism are still lacking; in particular, the hydrate enrichment factors are not, as yet, completely clear. In this study, we systemically characterize the geological controls on gas hydrate accumulation in the Shenhu area, including the sedimentary environment, gas sources, fluid and gas pathways, and reservoir-caprock system. We subsequently provide a quantitative evaluation of some critical factors influencing hydrate enrichment. The depositional environment in the study area was characterized by low energy (sedimentary hydrodynamic conditions), and anoxic environment, and the gas hydrate accumulations were closely associated with turbidites. The methane captured in the gas hydrates in the GMGS1 area and at the SHSC-4 and SHSC2-6 production test sites was mainly derived from the microbial reduction of CO2, while thermogenic gas was a more important source of hydrocarbon gases in the GMGS3 and GMGS4 areas. In addition, we used a combination of 8-slice spiral X-ray computed tomography (CT) and micro-CT techniques for the first time for the in-situ investigations of the microfractures and foraminifera in the hydrate cores. The results indicate that microfractures and foraminiferal shells are crucial to the occurrence and accumulation of gas hydrates in fine-grained sediments of the Shenhu area. Interestingly, microfractures were found to be more developed in the hydrate layers where most sediment particles were relatively small in size. Hydrate saturation increased with i) a decrease in the specific surface area of sediment grain, ii) an increase in the median pore size, and iii) increased foraminifera abundance in the reservoir. Our findings could help locate high-saturation gas hydrate layers ('sweet spot') in fine-grained marine sediments of the Shenhu area, South China Sea. Highlights: Microscopic factors influencing the hydrate enrichment are comprehensively discussed. A conceptional model for hydrate accumulation was proposed in the Shenhu area. Microfractures prefer to develop in the hydrate layers where the sediment particles have relatively small grain size. Thermogenic gas makes an important contribution to hydrate accumulation in turbidites connecting deep faults.